Bellydance - Dolphina (Goddesslife., 2005)
"Originally performed as part of fertility rituals and as a preparation for childbirth, bellydancing has now become one of America's best-loved fitness crazes. Bellydancing is a unique and fun way to keep fit and tone your entire body. It is a non-impact exercise that burns fat, increases flexibility, and complements the natural movement of the body. On top of the numerous physical benefits, women who bellydance say that it increases self-esteem and confidence. It's a unique way to exercise mind, body, and spirit."